Plasma Fractionation: Conditions and Challenges - Rambia, Ikhsan; Insyirah, Ariani; Claudiana, Nur Shelly Ester; Fath, Zulfa Tavira Al; Permadi, Najla Eksakta; Sriwidodo, Sriwidodo; Rustan, Mas Rahman (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Plasma is a blood component that has a role in treating various diseases, such as haemophilia and blood-clotting disorders. Plasma used for treatment is referred to as plasma-derived drug products (PDMPs), which are obtained through the plasma fractionation process. This study aims to explore the conditions of plasma fractionation in various countries and highlight some of the challenges faced by the plasma fractionation industry. The methods used include searching for articles published over the past decade from trusted sources, such as Google Scholar, PubMed, and ScienceDirect, using specific keywords. The results of literature studies related to plasma fractionation were obtained from 20 countries spanning several continents. The conditions and challenges faced in plasma fractionation in those countries differ. Some of the challenges faced are related to technology, regulation, plasma sources, human resources, and the economy. Currently, Indonesia is working with South Korea to build the first plasma fractionation facility. Therefore, the conditions and challenges faced by various countries can serve as a reference for Indonesia in preparing the factors that influence plasma fractionation development, in accordance with the World Health Organization (WHO) recommendations.